[32]π Fused Core‐Modified Heptaphyrin with Möbius Aromaticity. Issue 12 (4th February 2016) - Ghosh, Arindam; Chaudhary, Arvind; Srinivasan, A.; Suresh, Cherumuttathu H.; Chandrashekar, Tavarekere K.
Abstract: A new fused core‐modified 32π heptaphyrin with Möbius aromatic character is reported. The 1 H NMR data indicated a weak Möbius aromaticity at 298 K; however, at 213–183 K, the molecule predominates [4 n ]π Möbius conformation with strong diatropic ring current, which was further confirmed by X‐ray analysis. The protonation experiment led to preservation of the Möbius aromaticity at 298 K. Nevertheless, the experimental results were further supported by theoretical studies. Overall, this study represents the first example of Möbius aromatic fused core‐modified expanded porphyrin. Abstract : First example of a 32π fused core‐modified heptaphyrin, which exhibits Möbius aromaticity in solid, solution, and protonated state, is described. The rigid dithienothiophene (DTT) unit, flexible tripyrrane moiety, right combination of meso ‐aryl units, and reduction in the number of heteroatoms play major roles to achieve this conformation (see figure).